Effects of an AAC App with Transition to Literacy Features on Single-Word Reading of Individuals with Complex Communication Needs. (June 2020) - Caron, Jessica; Light, Janice; McNaughton, David
The purpose of this study was to investigate the effects of Transition to Literacy (T2L) software features (i.e., dynamic text and speech output upon selection of a graphic symbol) within a grid display in an augmentative and alternative communication (AAC) app on the single-word reading skills of five individuals with severe disabilities and complex communication needs. The study implemented a single-case multiple probe research design across one set of three participants. The same design was utilized with an additional set of two participants. During intervention, the T2L feature was activated for targeted words during a book reading activity. The dependent variable was the number of 10 target words correctly identified. With only limited exposure to the T2L feature, the five participants all demonstrated increased accuracy in identification of 10 target words. Four of the five participants generalized learning to use a text-only display for the 10 target words. This study provides preliminary evidence that redesigning AAC apps to include the provision of dynamic text combined with speech output can positively impact the single-word reading of participants. This adaptation in AAC system design could be used to support improved outcomes in both language and literacy.